57.5k views
4 votes
Y = ∫e^(−t) . sin^2(t) . 1/ t with laplace

1 Answer

2 votes

I'm guessing your supposed to compute the value of the integral


I=\displaystyle\int_0^\infty\frac{e^(-t)\sin^2t}t\,\mathrm dt

by way of Laplace transform.

The integral is equivalent to the transform of
\frac{\sin^2t}t when
s=1, since


\mathscr L_s\left\{\frac{\sin^2t}t\right\}=\displaystyle\int_0^\infty\frac{\sin^2t}te^(-st)\,\mathrm dt

Recall the frequency-domain integration property of the transform:


\mathscr L_s\left\{\frac{f(t)}t\right\}=\displaystyle\int_s^\infty F(\sigma)\,\mathrm d\sigma

where
F(s) is the Laplace transform of
f(t).

Let
f(t)=\sin^2t=\frac{1-\cos(2t)}2; then


F(s)=\frac12\left(\frac1s-\frac s{s^2+4}\right)

Next, it follows that


\mathscr L_s\left\{\frac{\sin^2t}t\right\}=\displaystyle\int_s^\infty F(\sigma)\,\mathrm d\sigma


\displaystyle=\frac{\ln\sigma^2-\ln(\sigma^2+4)}4\bigg|_(\sigma=s)^(\sigma\to\infty)


\displaystyle=\frac14\ln\left(1+\frac4{s^2}\right)

Get the value of
I by substituting
s=1:


\displaystyle\int_0^\infty\frac{e^(-t)\sin^2t}t\,\mathrm dt=\boxed{\frac{\ln5}4}

User Prapti
by
5.1k points